The Influence of Tiktok Usage Intensity and Digital Payments on Gen Z‘S Consumptive Behavior - Alya Pasha Berlianti; Aang Curatman (Interdisciplinary Social Studies, 2026)
The growth of platforms offering short video content such as TikTok and the rise of digital payments have changed the way people buy goods, especially for Generation Z. This study aims to find out the impact of the intensity of TikTok and digital payment use on Generation Z's consumptive behavior, both individually and simultaneously.  This study uses an associative quantitative approach with a Likert scale questionnaire (1-5). The research sample consisted of 150 active Gen Z respondents who used TikTok and had used digital payments. The data analysis technique used validity and reliability tests, classical assumption tests, and multiple linear regression using t and f tests. The results of this study show that the intensity of TikTok use has a positive and significant effect on consumptive behavior, digital payments also have a positive and significant effect on consumptive behavior, and these two variables simultaneously have a significant influence on the consumptive behavior of Gen Z. Findings show that the increase in the intensity of TikTok use, which is driven by exposure to TikTok content and the ease of digital transactions,  can exacerbate impulse buying and overconsumption tendencies among Gen Z. This research aims to contribute to the study of digital consumer behavior and serves as an input for financial and digital literacy education to reduce the consumerism tendencies of the younger generation.